The Involvement of OsPHO1;1 in the Regulation of Iron Transport Through Integration of Phosphate and Zinc Deficiency Signaling - Saenchai, Chorpet; Bouain, Nadia; Kisko, Mushtak; Prom-u-thai, Chanakan; Doumas, Patrick; Rouached, Hatem (Frontiers in Plant Science, 2016)
Plants survival depends on their ability to cope with multiple nutrient stresses that often occur simultaneously, such as the limited availability of essential elements inorganic phosphate (Pi), zinc (Zn) and iron (Fe). Previous research has provided information on the genes involved in efforts by plants to maintain homeostasis when a single nutrient (Pi, Zn or Fe) is depleted. Recent findings on nutritional stress suggest that plant growth capacity is influenced by a complex tripartite interaction between Pi, Zn and Fe homeostasis. However, despite its importance, how plants integrate multiple nutritional stimuli into complex developmental programs, and which genes are involved in this tripartite (Pi ZnFe) interaction is still not clear. The aim of this study was to examine the physiological and molecular responses of rice (Oriza sativa L.) to a combination of Pi, Zn and/or Fe deficiency stress conditions. Results showed that Fe deficiency had the most drastic single-nutrient effect on biomass, while the Zn deficiency-effect depended on the presence of Pi in the medium. Interestingly, the observed negative effect of Fe starvation was alleviated by concomitant Pi or PiZn depletion. Members of the OsPHO1 family showed a differential transcriptional regulation in response PiZnFe combinatory stress conditions. Particularly, the transcripts of the OsPHO1;1 sense and its natural antisense cis-NatPHO1;1 showed the highest accumulation under PiZn deficiency. In this condition, the Ospho1;1 mutants showed over-accumulation of Fe in roots compared to wild type plants. These data reveal coordination between pathways involved in Fe transport and PiZn signalling in rice which involves the OsPHO1; 1, and support the hypothesis of a genetic basis for Pi, Zn and Fe signalling interactions in plants.